The ICE Power Concept as Food Security Strategies at Cihambulu, Pabuaran, Subang, Jawa Barat: Food Strategy Analisys - Lesmana, Rosa; Sunardi, Nardi; Science, Kartono (ADPEBI, 2022)
Food security is the most important aspect in live, especially during covid 19 pandemic. The purpose of this research is to know the condition of food security in Cihambulu, Pabuaran, Subang as well as the food security strategies or the concepts can be applied to improve food security and public welfare at Cihambulu, Pabuaran, Subang, Jawa Barat. Type of the research is descriptive qualitative using a theoretical analysis approach – theories related to food security and ice power concept. The object of analysis is the citizen of Cihambulu, Pabuaran, Subang, Jawa Barat. Data collected by surveys, interviews, and observations. The results showed that the condition of food security in Cihambulu, Subang, Jawa Barat is in low level or below the safe limit, while the efforts that can be done are to maximize the use of house yards by planted that can meet the needs of home industry, and also provide entrepreneur training and education. And the business concept than can be applied is Ice Power concept which focuses on socio-social and cultural.